Impacts of regulation on eco-innovation and job creation - Jens Horbach (IZA World of Labor, 2020)
New environmental technologies (environmental/eco-innovations) are often regarded as potential job creators—in addition to their positive effects on the environment. Environmental regulation may induce innovations that are accompanied by positive growth and employment effects. Recent empirical analyses show that the introduction of cleaner process innovations, rather than product-based ones, may also lead to higher employment. The rationale is that cleaner technologies lead to cost savings, which helps to improve firms' competitiveness, thereby inducing positive effects on their market shares.
Keywords: Q52; Q55; J49; C25; 330; environmental innovation; employment; regulation